Carbon capture and utilization of fermentation CO2: Integrated ethanol fermentation and succinic acid production as an efficient platform. (15th November 2017) - Zhang, Quanguo; Nurhayati,; Cheng, Chieh-Lun; Nagarajan, Dillirani; Chang, Jo-Shu; Hu, Jianjun; Lee, Duu-Jong
Highlights: CO2 generated and released from ethanol fermentation process was captured. C. vulgaris and A. succinogenes were used to capture the fermentation CO2 . CO2 fixation rate of C. vulgaris was 2.06 g/L-d with 1.2 g/L biomass production. The highest CO2 rate by A. succinogenes was 388.8 g/L-d in 2-L reactor. Carbon fixation by A. succinogenes is 188 times higher than that of C. vulgaris. Abstract: Dark fermentative bioethanol production process yields carbon dioxide (CO2 ) and organic acids as by-products. The so-yielded CO2 is a nearly saturated gas of high CO2 purity, which is commonly utilized in food industries as supplements. The potential utilization pathways for the CO2 generated and released from the ethanol fermentation process (denoted as "fermentation CO2 ") include production of biofuels by CO2 fixation of microalgae and succinic acid fermentation by non-photosynthetic microorganisms. This study compared the performances of these two CO2 fixing pathways using Chlorella vulgaris or Actinobacillus succinogenes cultures. The highest carbon fixation rate achieved by Actinobacillus succinogenes was 388.8 g/L-d in 2-L reactor, which is about 188 times to that by Chlorella vulgaris (2.06 g/L-d) in the reactor at the same volume. This study ultimately demonstrated the advantages of adopting succinic acid production process compared to those frequently addressed in literature using microalgae-based biofuels.